2000
DOI: 10.1177/0265407500174007
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Perceptions of Conflict in Romantic Relationships

Abstract: The purpose of the present investigation was to replicate and extend what is known about sex differences in conflict management behaviors. In particular, two main questions were addressed in two studies: (1) How do men and women perceive their own and their partner's conflict management behaviors? (2) Is there a relationship between relationship satisfaction and self-partner congruence of perceptions? Consistent with the past literature, the findings indicated that women perceived themselves to be significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
2
14

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 33 publications
6
26
2
14
Order By: Relevance
“…Although some studies have found gender differences in conflict strategies (Feldman & Gowen, 1998;Hojjat, 2000;Schwarzwald & Koslowsky, 1999), gender differences were not found for either positive or negative conflict strategies in the current study. This finding supports theory and research suggesting that the gender gap may be closing in some areas of relationship development (Shulman, Levy-Shiff, Kedem, & Alon, 1997).…”
Section: Discussioncontrasting
confidence: 96%
“…Although some studies have found gender differences in conflict strategies (Feldman & Gowen, 1998;Hojjat, 2000;Schwarzwald & Koslowsky, 1999), gender differences were not found for either positive or negative conflict strategies in the current study. This finding supports theory and research suggesting that the gender gap may be closing in some areas of relationship development (Shulman, Levy-Shiff, Kedem, & Alon, 1997).…”
Section: Discussioncontrasting
confidence: 96%
“…Fakat boyun eğme ve geri çekilme alt boyutları evlilik uyumu ile anlamlı bir ilişki göstermemektedir. İlgili yazında da, yapıcı çatışma çözüm yöntemlerinin evlilik uyumu ya da doyumu ile olumlu yönde ilişkili olduğu, fakat yıkıcı çatışma çözüm yöntemlerinin ise evlilik uyumu ya da doyumu ile olumsuz yönde ilişkili olduğu pek çok çalışma ile gösterilmiştir (örn., Christensen ve Heavey, 1990;Fincham, 2003;Heavey, Layne ve Christensen, 1993;Hojjat, 2000). Fakat beklenenden farklı olarak boyun eğme ve geri çekilme evlilik uyumu ile anlamlı bir ilişki göstermemiştir.…”
Section: Discussionunclassified
“…Bu maddeleri geliştirmek amacıyla 5 sosyal psikolog tarafından ilgili yazın incelenmiş, Türkiye örnekleminde henüz geçerlik güvenirliği ispatlanmamış farklı ölçek maddeleri de incelenmiştir (örn., Hojjat, 2000;Kurdek, 1994a). Ayrıca, birinci yazar evli ve evli olmayan romantik ilişki içindeki 20 birey ile görüşmeler yapmış ve bu görüşmeleri ses kaydına almıştır.…”
Section: Veri Toplama Araçları Ve İşlemunclassified
“…Mada neka istraživanja (Hojjat, 2000) sugerišu da su žene objektivniji procenjivači konflikata u partnerskom odnosu od muškaraca, te da se njihove procene u većoj meri slažu sa procenama nezavisnih posmatrača, iskazivanje visokog globalnog i dijadnog zadovoljstva na ispitanom uzorku žena (ma koliko da je on brojan) bi moglo biti posledica smanjene iskrenosti, odnosno davanja socijalno poželjnih odgovora kod velikog broja ispitanica, što onda utiče i na iskrivljivanje svih dobijenih rezultata, odnosno utvrđenih nalaza o relacijama bračnog zadovoljstva i izbora strategija suočavanja sa stresom. Međutim, pošto je ispitivanje bilo na dobrovoljnoj osnovi, a nemamo uvid u broj odbijenih uključivanja u ispitivanje, moguće je i da žene koje su nezadovoljne svojim bračnim odnosom nisu bile spremne ni da se uključe u ispitivanje.…”
Section: Metodunclassified